A proteção internacional do meio ambiente como um direito humano fundamental - Souza, Karla Karolina Harada (2015)
This dissertation aims to identify the environment as a fundamental human right, considering it as an extension of the right to life and inherent to the dignity of the human person. Initially, there was a discourse about human rights, and later on fundamental rights, analysing their concepts and understandings of various authors on the subject, and the implications of its legal status, so that reaching these definitions, we could qualify and conceive the right to the environment as a fundamental human right. Following, we spoke about the laws, international treaties and conventions regarding human rights and concerning to environmental protection, showing that in the present international legal system, these two subjects, namely, human rights and the environment, are treated separately, mainly due to the historical moment in which they were developed and drafted. We also examined the internalization and constitutionalising movements of these rights, and their hierarchy within the domestic laws of the countries. We also evaluated the treatment and the evolution of human rights in the international level, so that through a holistic understanding, we can say that considering the protection of the environment as a fundamental human right, the right to the environment should be protected more completely, especially at an international level. In the absence of a specific international courts and bodies for the protection of the environment, those rights could be brought before international courts and human rights organisms. Finally, after all the conceptual theories and studies on the understanding of the evolution and structure of the environment in the world s legal system, we support the interconnection of these objects, guaranteeing treatment, status and strength of a fundamental human right to the defence and protection of the environment